2022
DOI: 10.3390/ijms23168982
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Immunity: Natural Infection Compared with Vaccination

Abstract: Recently, the protective and/or pathological role of virus-specific T cells in SARS-CoV-2 infection has been the focus of many studies. We investigated the anti-spike IgG levels and SARS-CoV-2-specific T cells in 125 donors (90 vaccinated with four different vaccine platforms, 16 individuals with a previous natural infection, and 19 not vaccinated donors who did not report previous SARS-CoV-2 infections). Our data show that anti-spike IgG titers were similar between naturally infected subjects and those vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Following a 2-dose mRNA vaccination schedule, robust cellular responses are observed in the majority of patients with hematologic malignancies, including patients with CLL, lymphomas, and recipients of CD19-directed CAR T cell therapy ( Figure 1 C). [ 29 , 45 , 46 , 47 , 48 ] It is suggested that these responses depend on vaccine type, with better responses induced by mRNA-1273 vaccination compared to BNT162b2 [ 43 , 48 , 49 ]. Cellular responses also differ between patient groups.…”
Section: Immunogenicity Of Covid-19 Vaccination In Patients With Hema...mentioning
confidence: 99%
“…Following a 2-dose mRNA vaccination schedule, robust cellular responses are observed in the majority of patients with hematologic malignancies, including patients with CLL, lymphomas, and recipients of CD19-directed CAR T cell therapy ( Figure 1 C). [ 29 , 45 , 46 , 47 , 48 ] It is suggested that these responses depend on vaccine type, with better responses induced by mRNA-1273 vaccination compared to BNT162b2 [ 43 , 48 , 49 ]. Cellular responses also differ between patient groups.…”
Section: Immunogenicity Of Covid-19 Vaccination In Patients With Hema...mentioning
confidence: 99%
“…The development, in a short time, of new vaccines to prevent SARS-CoV-2 infection was one of the most relevant scientific landmark achievements in this context [ 2 , 3 ]. Despite the administered COVID-19 vaccination platforms ensuring the development of specific humoral and cellular immune responses, protecting against severe disease symptoms [ 4 , 5 , 6 , 7 ], several adverse effects were reported, even if most of them were classified as mild reactions [ 8 ]. Furthermore, in most patients reporting adverse effects, no events occurred after a second vaccination, demonstrating that most of the reported reactions were not allergic events but vasovagal and anxiety signs.…”
Section: Introductionmentioning
confidence: 99%
“…Com o desenvolvimento de diferentes vacinas, diversos protocolos heterólogos foram aplicados a fim de gerar respostas imunológicas mais eficazes 1 . Nesse cenário, foi amplamente questionada a eficácia das vacinas e dos protocolos vacinais diante da proteção gerada pela infecção natural 2 .…”
unclassified